HUBUNGAN ANTARA KEMAMPUAN BTQ SISWA DENGAN PRESTASI BELAJAR MEREKA DALAM MATA PELAJARAN AL-QURAN HADIS - Nurlaela, Siti; Millah, Saepul; Rohman, Ahmad Abdur (Jurnal Penelitian Pendidikan Islam, 2015)
The purpose of this study was to analyze the relationship between students' ability to study with learning achievement in the subjects of Al-Qur'an Hadith. The results of the study can be summarized as follows: 1) The ability to read and write the Koran in class IV Madrasah Ibtidaiyah Mekarsari, Jatinagara District, Ciamis Regency is categorized as high. This is evident from the results of oral and written tests with an average value of 3.85 which is in the interval 3.6 - 4.5; 2) Student learning achievement in the subject of Al-Quran Hadith in Madrasah Ibtidaiyah Mekarsari, Jatinagara District, Ciamis Regency is categorized as good. This is evident from the results of written tests with an average value of 79, this rating scale is at intervals of 71-79. 3) There is a relationship between students' learning abilities in reading and writing the Koran with student learning achievement in the Quranic Hadith subjects in Madrasah Ibtidaiyah Mekarsari, Jatinagara District, Ciamis Regency, is 49%. This means that there are still 51% other factors that affect their learning achievement in Al-Quran Hadith subjects.